2019
DOI: 10.1002/solr.201900280
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Toward Extending the Near‐Infrared Photovoltaic Response of Perovskite Solar Cells

Abstract: The emerging perovskite materials present great opportunities for cost‐saving and efficient photovoltaic devices. However, perovskite solar cells (PSCs) suffer from the limitation of short optical absorption edge, resulting in most of the near‐infrared (NIR) light being wasted. Recently, strategies toward broadening the NIR spectra response and further improve the power conversion efficiency of PSCs have attracted extensive attention. In this review, the unique features of perovskite materials are first introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 116 publications
(172 reference statements)
0
6
0
1
Order By: Relevance
“…For instance, it is reported that up to 40% of the thermodynamic loss in PVs occurs due to carrier thermal relaxation . Furthermore, the spectral windows of many PVs have a maximum onset of photogeneration around 800 nm, which means that nearly the entire near-infrared (NIR) spectrum is reflected or lost as waste heat …”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is reported that up to 40% of the thermodynamic loss in PVs occurs due to carrier thermal relaxation . Furthermore, the spectral windows of many PVs have a maximum onset of photogeneration around 800 nm, which means that nearly the entire near-infrared (NIR) spectrum is reflected or lost as waste heat …”
Section: Introductionmentioning
confidence: 99%
“…To realize efficient TSCs, the low-band gap photovoltaic materials selected as the rear active layer should have strong absorption of near-infrared light. For current perovskite-based TSCs, Si, CIGS, and low-band gap perovskite were usually utilized as rear subcells. The state-of-the-art perovskite/Si, perovskite/CIGS, and perovskite/perovskite TSCs achieved a high PCE of 29.1%, 22.4%, and 24.8%, respectively, demonstrating the promising prospect of perovskite-based TSCs. ,, Besides this, perovskite/organic TSCs combining a wide-band gap perovskite and a low-band gap organic photovoltaic is another favorable choice for perovskite-based TSCs, owing to the similar fabrication process and architecture characteristics for PerSCs and organic solar cells (OSCs). On the other hand, most efficient OSCs have narrower band gaps compared with PerSCs for wider absorption but suffer from weak absorption of visible light, particularly for the wavelength range of 350–500 nm, resulting from the intrinsic intramolecular charge transfer characteristic of organic semiconductors .…”
mentioning
confidence: 99%
“…The high near‐infrared transmittance makes the device an ideal candidate as a top cell in tandem applications with Si bottom cells, as it allows more low‐energy photons to pass through. [ 47 ] As shown in Figure 6b and Table 2 , the best semitransparent perovskite device demonstrates efficiency of 17.55% with a V oc of 1.11 V, a J sc of 22.15 mA cm −2 , and an FF of 71.40%. The initial efficiency of the silicon solar cell was17.85% with a V oc of 0.70 V, a J sc of 36.90 mA cm −2 , and an FF of 69.10%, while the efficiencies retained to 6.27% after using the filter.…”
Section: Resultsmentioning
confidence: 99%